2016
DOI: 10.29252/jafm.09.06.25908
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Rotor Wake of Horizontal Axis Wind Turbine under Yawed Condition

Abstract: The wake and the lack of existing velocity behind the wind turbine affect the energy production and the mechanical integrity of wind turbines downstream in the wind farms. This paper presents an investigation of the unsteady flow around a wind turbine under yawed condition. The simulations and experimental measures are made for the yaw angle rotor 30° and 0°. The wind velocity is 9.3 m/s and the rotation velocity rotor of the wind turbine in 1300, 1500 and 1800 rpm. The wind turbine rotor which is modeled is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The turbulence model used with IDDES is the SST due to pressure gradient adaptability and flow separation predictability with compared to the other two-equation models. The complete transport equations for SST-IDDES model are given by Noura et al 20…”
Section: Methodsmentioning
confidence: 99%
“…The turbulence model used with IDDES is the SST due to pressure gradient adaptability and flow separation predictability with compared to the other two-equation models. The complete transport equations for SST-IDDES model are given by Noura et al 20…”
Section: Methodsmentioning
confidence: 99%
“…Offset yaw angles have been studied to test potential increases to downstream wind turbines. It is interesting that for wind farms with an array of turbines, Miao, Li [9] , Noura, Dobrev [10] and Xinghui Dong and Hui Wang [11] found purposely angling upstream wind turbines can increase the overall power yield. Tip speed ratio (λ), which is defined as the ratio of wind turbine blade tip velocity to the wind speed, is a crucial value when wind turbine design is considered.…”
Section: Introductionmentioning
confidence: 99%
“…The results of large eddy simulation showed that the dimensionless mean velocity and Reynolds stress curves in the wake of HAWT show selfsimilarity through an appropriate choice of characteristic scales of velocity and length. In recent years, numerous efforts have been spent on the wake characteristics and the establishment of wake models for HAWTs (Noura et al 2016;Belkheir et al 2012;Dahmouni et al 2017;Kabir et al 2019;Qian et al 2022). However, the research on the wake characteristics of VAWT is not as extensive as that of HAWTs (Paraschivoiu 2002).…”
Section: Introductionmentioning
confidence: 99%